Предмет: Алгебра,
автор: Аноним
Решите уравнение: 5х(х-3)²-5(х-1)³+15(х+2)(х-2)=5
Пожалуйста буду очень благодарна!
Ответы
Автор ответа:
0
5х(х-3)²-5(х-1)³+15(х+2)(х-2)=5,
5х(х²-6х+9)-5(х³-3х²+3х-1)+15(х²-4)=5,
5х³-30х²+45х-5(х³-3х²+3х-1)+15х²-60=5,
5х³-30х²+45х-5х³+15х²-15х+5+15х²-60=5,
-30х²+45х+15х²-15х+15х²-60=0,
0+30х-60=0,
30х-60=0,
30х=60,
х=60:30,
х=2.
Ответ: 2.
5х(х²-6х+9)-5(х³-3х²+3х-1)+15(х²-4)=5,
5х³-30х²+45х-5(х³-3х²+3х-1)+15х²-60=5,
5х³-30х²+45х-5х³+15х²-15х+5+15х²-60=5,
-30х²+45х+15х²-15х+15х²-60=0,
0+30х-60=0,
30х-60=0,
30х=60,
х=60:30,
х=2.
Ответ: 2.
Похожие вопросы
Предмет: Русский язык,
автор: varvara846
Предмет: Математика,
автор: pushkarkristina077
Предмет: Математика,
автор: milenababayan555
Предмет: Математика,
автор: oTTтИмИсТ
Предмет: Геометрия,
автор: anulia99